Biochar-Based Filter for Methylene Blue and Methyl Orange Adsorption - Ghenwa Kataya; May Issa; Akram Hijazi; Mikhael Bechelany (Proceedings)
Water, being essential for life, necessitates urgent protective measures, particularly in treating existing polluted water to safeguard public health and ecosystems [...]